2015
DOI: 10.1111/jbi.12534
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution patterns of plague hosts: point pattern analysis of the burrows of great gerbils in Kazakhstan

Abstract: AimThe spatial structure of a population can strongly influence the dynamics of infectious diseases, yet rarely is the underlying structure quantified. A case in point is plague, an infectious zoonotic disease caused by the bacterium Yersinia pestis. Plague dynamics within the Central Asian desert plague focus have been extensively modelled in recent years, but always with strong uniformity assumptions about the distribution of its primary reservoir host, the great gerbil (Rhombomys opimus). Yet, while cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Spatial structure of rodent populations has been recognized as an important factor for the invasion and spread of infectious agents (Rotshild 1975 , Keeling 1999 , Wilschut et al 2015 ). Analyzing the distribution of the burrows of great gerbils ( Rhombomys opimus ) in Kazakhstan, Wilschut et al ( 2015 ) concluded that spatial clustering of occupied burrows should be considered to assess its significance for plague transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial structure of rodent populations has been recognized as an important factor for the invasion and spread of infectious agents (Rotshild 1975 , Keeling 1999 , Wilschut et al 2015 ). Analyzing the distribution of the burrows of great gerbils ( Rhombomys opimus ) in Kazakhstan, Wilschut et al ( 2015 ) concluded that spatial clustering of occupied burrows should be considered to assess its significance for plague transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial structure of rodent populations has been recognized as an important factor for the invasion and spread of infectious agents (Rotshild 1975 , Keeling 1999 , Wilschut et al 2015 ). Analyzing the distribution of the burrows of great gerbils ( Rhombomys opimus ) in Kazakhstan, Wilschut et al ( 2015 ) concluded that spatial clustering of occupied burrows should be considered to assess its significance for plague transmission. In another study, an investigation of plague outbreaks in prairie dog ( Cynomys ludovicianus ) populations, the authors argued that plague can persist in the highly susceptible hosts because their movement is very constrained (Salkeld et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…All squares were located in one so-called ‘sector’ ( Fig. 1 ), a monitoring unit of the plague monitoring stations in Kazakhstan, approximately 9.3 km by 9.8 km in size ( Wilschut et al, 2013b , Wilschut et al, 2015 ). The squares are all located in the older part of the river Ili delta consisting of floodplains covered by river sediments, scattered sand dunes and semi-arid vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…At present, the methods of studying population spatial patterns include hierarchical analysis of variance, species-juxtaposition and point pattern analysis. Among them, point pattern analysis has been widely used for studying the spatial distribution patterns of plant populations [9,29], animal populations [30,31] and geographical landscapes [32,33].…”
Section: Introductionmentioning
confidence: 99%